Recent feminist research in US geography - Altha J. Cravey (Belgeo)
Feminist research in the US is vibrant, diverse, and innovative. I explore practical ways US-based feminists sustain themselves, and introduce research in political geography and migration studies. Recent work in these areas expands dialogue between political and feminist geographers, and sharpens the political edge of a larger collective feminist project aligned with activists and scholars worldwide. These works explicitly consider power while pursuing feminist action. In migration studies, the impact of feminist ideas is evident in the connections among migration, gender, and globalization. I argue that the greatest challenge for US-based feminist geographers is to maintain a political edge. To do so, we must attend to the global scope of the discipline ; encourage multi-sited, multi-scalar collaborative research ; nurture alliances with a broad spectrum of activists including anti-war, anti-imperialist, anti-racist, labor, sexuality, and environmental activists ; and creatively imagine political projects from various theoretical angles. In short, while our feminist theorizing and feminist actions may be heterogeneous, we must also seek – and constantly refine – a collective feminist project.